A CRITICAL STUDY OF DESAGATI CLANS OF KARNATAKA - Basusab, Bullannavar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The decline of royal kingdoms, gave room to political instability, then the people felt insecure. There was a serious question of religion, language, or culture being discarded A group of families called 'Desgati families' emerged, they stepped forward to preserve these values. The owner of the land was called 'Desai'; the word 'des' in the word Desagati is a Sanskrit word whose meaning is country. The word 'Gati' was added to this word and transformed into Desagati. The feudal lords who ruled locally belonged to the Desagati family. They lived a life of wealth, court, war, luxury, religion, culture, and literature, which played an important role in giving social contribution. Desgati families, who were at the helm of local administration, became intermediaries between the masses and the government. When the British government implemented new land tenure in Karnataka, a new class of landowners was created. This class was also composed of upper castes. They are Brahmin, Jain, Kshatriya, Lingayat, Ganiga, and Panchamasali. The Ruddy community became a tribal family. They are Desai, Nad Gowda, Paymaster, Kulkarni, Patil. They will be recognized as belonging to the Desagati family by the above names. Desagatis existed to benefit from British colonialism. Apart from the work of internal security, judiciary, military organization, and revenue collection, he lived a comfortable life with the income from war tax, commercial tax, and hired local officials like Shekhadar, Karakoona, Havaldar, Desh Kulkarni, and Patil to help him in administration. Desgati families had to follow the social values such as public welfare, social stability, and protection and punishment of the guilty, which was their main duty.